1986
DOI: 10.1083/jcb.102.5.1679
|View full text |Cite
|
Sign up to set email alerts
|

Aster-free spindle poles in insect spermatocytes: evidence for chromosome-induced spindle formation?

Abstract: Abstract. Tipulid spermatocytes form normally functioning bipolar spindles after one of the centrosomes is experimentally dislocated from the nucleus in late diakinesis (Dietz, R., 1959, Z. Naturforsch., 14b:749-752; Dietz, R., 1963, Zool. Anz. Suppl., 23:131-138; Dietz, R., 1966, Heredity, 19:161-166). The possibility that dissociated pericentriolar material (PCM) is nevertheless responsible for the formation of the spindle in these cells cannot be ruled out based on live observation. In studying serial sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…Observations of bipolar spindle assembly in cells that lack centrosomes have revealed the existence of a second mechanism for spindle pole formation, even in cells that normally contain centrosomes (for review, see Compton 2000). Findings, some dating back almost 40 years, that male and female meiotic cells can form bipolar acentrosomal spindles challenged the notion that centrosomes are needed for the establishment of spindle bipolarity (Dietz 1966;Steffen et al 1986). More recent work with Xenopus egg extracts has revealed that bipolar spindles will assemble from initially randomly oriented microtubules assembled in the vicinity of chromatin, be it chromosomes or beads coated with DNA fragments (Heald et al 1996(Heald et al , 1997.…”
Section: The Role Of the Centrosomes In Determining Spindle Polaritymentioning
confidence: 99%
“…Observations of bipolar spindle assembly in cells that lack centrosomes have revealed the existence of a second mechanism for spindle pole formation, even in cells that normally contain centrosomes (for review, see Compton 2000). Findings, some dating back almost 40 years, that male and female meiotic cells can form bipolar acentrosomal spindles challenged the notion that centrosomes are needed for the establishment of spindle bipolarity (Dietz 1966;Steffen et al 1986). More recent work with Xenopus egg extracts has revealed that bipolar spindles will assemble from initially randomly oriented microtubules assembled in the vicinity of chromatin, be it chromosomes or beads coated with DNA fragments (Heald et al 1996(Heald et al , 1997.…”
Section: The Role Of the Centrosomes In Determining Spindle Polaritymentioning
confidence: 99%
“…In addition, there is much accumulated evidence of acentrosomal meiotic systems in animal cells, such as mouse (Calarco-Gillam et al 1983), Xenopus (Heald et al 1996) and Drosophila (Matthies et al 1996). Furthermore, physical displacement of centrosomes from the nucleus in crane fly spermatocytes, or laser ablation of both centrosomes during prophase in monkey CVG-2 cells by laser microsurgery, does not disrupt bipolar spindle assembly (Steffen et al 1986;Khodjakov et al 2000). The observation that cells within a developing animal which normally contain centrosomes could, in fact, build a functional spindle in the complete absence of these organelles was confirmed genetically through removing, first core centrosomal and then core centriolar, proteins in fruit flies.…”
Section: Centrosome-nucleated Mtsmentioning
confidence: 99%
“…In spindle pole formation, the MTOC is the key player, be it focal in animal cells or diffuse-even invisible-in higher plant cells. Significantly, studies by Roland Dietz reported for primary crane fly spermatocytes that the centrioles could be displaced from the late diakinesis nucleus by flattening the cell; nevertheless, such cells assembled functional bipolar spindles (reviewed in [42]). Furthermore, exacting electron microscopy of such cells did not find accumulations of pericentriolar material (PCM) at these spindle poles; the PCM stayed with the centrioles [42].…”
Section: Centrioles Versus Centrosomesmentioning
confidence: 99%
“…Significantly, studies by Roland Dietz reported for primary crane fly spermatocytes that the centrioles could be displaced from the late diakinesis nucleus by flattening the cell; nevertheless, such cells assembled functional bipolar spindles (reviewed in [42]). Furthermore, exacting electron microscopy of such cells did not find accumulations of pericentriolar material (PCM) at these spindle poles; the PCM stayed with the centrioles [42]. In addition, for spermatocyte meiosis in the silkworm moth Bombyx mori the centrioles were not associated with astral fibres and were substantially separated from the spindle poles at metaphase [41].…”
Section: Centrioles Versus Centrosomesmentioning
confidence: 99%